KONSEP DASAR PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH INKLUSI - Erik Purwanti; Difa'ul Husna; Amalia Ririh Pertiwi; Purwaningsih Purwaningsih (Sekolah Tinggi Pariwisata Mataram, 2021)
Education is a process of changing one’s attitude and behavior which is most important for every human being to achieve his welfare in social life and in various other matters. Especially for children who have special disabilities or children with special needs (ABK). Basically, children who have special disabilities do need more adequate supervision and learning. With the existence of this inclusive school, children with special needs can experience the world of education according to what they should get in education like children in general. This inclusive school can be a place for children with special needs to learn and play without discrimination with other children to get the same education. Especially with education that teacher Islamic religious learning as an educational support that aims to shape the characteristics of students who have special backwardness in in order to still be able ti achieve a happy life in the afterlife.